2016
DOI: 10.5539/ijms.v8n2p128
|View full text |Cite
|
Sign up to set email alerts
|

Social Media Marketing Perspectives in the Organization in Morelia, Mexico

Abstract: Social media marketing (SMM) is a reality in contemporary society. This research presents a review of the literature on the phenomenon of SMM to establish the challenges and opportunities social media faces. Subsequently, the digital inclusion in Mexico is discussed roughly focusing on the situation of SMM in the organization in Morelia. The purpose of this paper is to contextualize the use of social media and establish the challenges and opportunities of inclusion in communication strategies and marketing in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…The foregoing shows that Mexico has the capabilities to develop the area of CMSN and that access is neither restricted nor limited for those entrepreneurs who want to launch into this activity. Then concludes Madrigal Moreno et al (2016) in a study that it is confirmed that the contemporary society has established the conditions to implement properly social media marketing in Morelia.…”
Section: Content Marketing and Social Network (Cmsn)mentioning
confidence: 75%
“…The foregoing shows that Mexico has the capabilities to develop the area of CMSN and that access is neither restricted nor limited for those entrepreneurs who want to launch into this activity. Then concludes Madrigal Moreno et al (2016) in a study that it is confirmed that the contemporary society has established the conditions to implement properly social media marketing in Morelia.…”
Section: Content Marketing and Social Network (Cmsn)mentioning
confidence: 75%
“…Digital marketing is used at every point of the consumer's buying process, from brand awareness to buy enchantment and product facilitation guidance, brand use instruction, and management of postpurchase customer service, according to Stone and Woodcock (2013). In order to reach customers, social network advertising, according to Moreno et al, (2016), utilizes communication channels for marketing and serves as a replacement for traditional marketing tactics. These results are congruent with research by Hassan et al, (2015), who discovered that social networking is a powerful marketing tool that draws consumers and influences their purchasing decisions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…There is an explanation for this change in shopping behavior. Studies conducted Madrigal Moreno et al (2016) revealed that internet technology has changed human lifestyles by providing increased welfare through various product choices, lower prices, unlimited access to information, and expanding distribution channels. Other studies have also shown that shopping through technology can be done without the need for direct meetings between sellers and buyers (Ha et al, 2015), thereby reducing obstacles in the transaction process (Öztamur & Karakadılar, 2014) Figure 1.…”
Section: Introductionmentioning
confidence: 99%